Virtual Classroom Usage and User Perception for English Learning as a Second Language at Universities in Lima, Peru - La Torre Castillo, Carlos Celso (International Journal of Emerging Technologies in Learning (iJET), 2021)
A more extensive use of virtual tools in teaching-learning processes needs a professors’ and students’ proactive attitude, positive experiences, and improvement in their implementation. A cross-sectional study was carried out to know the perceptions of private university students from Lima on the use of the necessary elements for an English language virtual classroom. The sample was composed of 150 accounting students from five universities, whose perceptions on virtual classroom elements were assessed and compared to their previous experiences. Most students were in favor of using the virtual classroom and its different elements, and those who had a previous experience with virtual classrooms were more in favor of using reminders, chats, forums, e-mails and online exercises (p<0,05). In sum, most students were in favor of using the virtual classroom and having a previous experience favors a more positive perception towards online learning tools.